Attitudes towards the male contraceptive pill in men and women in casual and stable sexual relationships. Issue 3 (1st July 2009) - Eberhardt, Judith; van Wersch, Anna; Meikle, Neil
Abstract : Background and methodology: Men's and women's attitudes towards the male contraceptive pill and their trust in the effective use of the male pill were investigated, as well as the associated variables of reported health behaviours, perceived self-efficacy and type of sexual relationship, using a questionnaire survey. Results: Although both sexes had a favourable attitude towards the male pill, females had a more positive attitude than men. Conversely, women had less trust that men would use the male pill effectively. Males in stable sexual relationships were more positive about the male pill than those in casual sexual relationships. Gender, relationship type and trust in the effective use of the male pill reliably predicted attitude towards the male pill. High perceived self-efficacy was related to engaging in more health behaviours, and in men a positive association between health behaviours and attitude towards the male pill has been found. Discussion and conclusions: A positive attitude towards the male pill does not automatically imply that the individual is confident about its effective use. Once the male pill is widely available, promotional campaigns could target not only men but also their female partners, as the latter tend to come into contact with health services more frequently. In order to increase confidence in effective implementation, a variety of presentations of the male pill should be made available in line with individual needs and lifestyles.